Mirror-Image Dextrocardia - McGrath, Brent M; West, Peter (DALHOUSIE MEDICAL JOURNAL, 2012)
There are several variants of a rightward-positioned heart. In mirror-image dextrocardia, the anterior-posterior relationship of the cardiac chambers and great vessels and maintained; however, their left-to-right orientation is reversed. This form of dextrocardia most often occurs in the context of situs inversus totalis in which the other major visceral organs (including the stomach and liver) are reversed. Mirror-image dextrocardia is largely regarded as a normal variant with intracardiac malformations and pathology no more frequent than those of the general population. Physical exam, CXR, and ECG are diagnostic of mirror-image dextrocardia.